Mental health characteristics of exonerees: a preliminary exploration - Alexander-Bloch, Benjamin (Psychology, crime & law, 2020)
The current study provides a preliminary examination of descriptive data on the mental health and sleep problems of exonerees across the United States. Thirteen male exonerees were recruited from Innocence Network-affiliated organizations. Participants completed surveys on symptoms of anxiety, depression, posttraumatic stress disorder (PTSD), and sleep problems. Participants reported spending an average of 15.75 years in prison (SD = 9.51) for their now-exonerated conviction. They had been released through their exoneration an average of 9.85 years ago (SD = 5.70). Nearly half of participants reported clinically significant levels of depression, anxiety, and PTSD symptoms, which were significantly intercorrelated. Greater time since release from prison was associated with significantly lower levels of depression and anxiety (p < .05), but only marginally related to lower PTSD symptoms (p < .10). On average, exonerees reported 5.8 h of sleep per night and four unique sleep disturbances per week. The findings provide preliminary evidence supporting the need for post-incarceration mental health services for exonerated prisoners. Further research is needed with larger sample sizes, as well as comparisons with non-exonerated former inmates.